Advances in brain barriers and brain fluid research and news from Fluids and Barriers of the CNS. Issue 1 (December 2015) - Drewes, Lester; Jones, Hazel; Keep, Richard
Abstract Research into brain barriers and brain fluids has been advancing rapidly in recent years. This editorial aims to highlight some of the advances that have improved our understanding of this complex subject. It also brings you news of developments for Fluids and Barriers of the CNS including a new affiliation between the journal and the International Society for Hydrocephalus and CSF disorders.